Mapping hole mobility in PTB7 films at nanoscale - Yedrissov, A.; Ilyassov, B.; Alekseev, A.; Hedley, G J; Samuel, D W; Kharintsev, S. (IOP Publishing, 2019)
The nanoscale hole mobility in organic semiconducting polymer PTB7 is quantified by using conductive-AFM (C-AFM) measurements in space charge limited (SCLC) regime. The obtained current map of the neat PTB7 film is explained in terms of non-uniform built-in voltage and variations of hole mobility. For mobility estimation, the semi-empirical model of SCLC, known from previous works, was modified and applied. It is found that the values of built-in voltage in C-AFM measurements are usually several times larger than ones derived from macroscopic measurements. It is also shown that value of hole mobility in PTB7 film depends on location and varies in more than two times. These mobility variations are connected with nanoscale film structure revealed by other methods.